DSN-MUI Fatwas and Islamic Retirement Planning: A Maqāṣid al-Sharīʿah Review of Financial Security among Non-Civil Servant Lecturers in Indonesia - Ahyani, Hisam; Harahap, Arifuddin Muda; Mustofa; Rahim, Abdul; Tanjung, Indra Utama; Mutmainah, Naeli; Gumel, Salisu (MUI Sulawesi Selatan, 2026)
Retirement preparedness among non-civil servant lecturers in Indonesia has emerged as a critical issue due to the absence of comprehensive institutional pension schemes. This study critically examines the role of fatwas issued by the Dewan Syariah Nasional–Majelis Ulama Indonesia (DSN-MUI) in shaping Islamic retirement financial planning, employing a Maqāṣid al-Sharīʿah framework. It focuses particularly on fatwas related to sharia investment, partnership contracts (muḍārabah and mushārakah), and Islamic capital market practices. Using a qualitative socio-legal approach, this research integrates normative analysis of DSN-MUI fatwas with empirical data from interviews with non-civil servant lecturers across several regions in Indonesia. The findings reveal a normative–practical gap: while DSN-MUI fatwas provide comprehensive ethical and legal guidance for halal financial planning, their application in retirement strategies remains partial and adaptive. Lecturers tend to adopt halal investment, productive assets, and entrepreneurial activities; however, these practices are not always directly grounded in specific fatwa reasoning but are mediated by general Islamic economic ethics. From a maqāṣid perspective, this reflects the realization of ḥifẓ al-māl, yet also indicates limitations in the operationalization of fatwa authority in everyday financial decision-making. This study argues that DSN-MUI fatwas function not only as doctrinal legal products but also as instruments of financial governance whose effectiveness depends on institutional dissemination and socio-economic context. By highlighting the gap between normative fatwa frameworks and lived financial practices, this research contributes to contemporary fatwa discourse, particularly in strengthening the role of fatwa governance in Islamic retirement planning and financial policy development.